THE SOURCES OF RADIATION IN THE SHORT-WAVE RANGE ON THE BASIS OF II-VI HETEROLAYERS - Slyotov, Mikhail; Slyotov, Alexey (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
The possibility of obtaining zinc selenide and zinc sulfide layers of hexagonal modification by isovalent substitution method is shown. They are characterized by intensive luminescence which is formed by the dominant annihilation of bound excitons for α-ZnSe and recombination on donor-acceptor pairs for α-ZnS. The resulting radiation covers the violet wavelength range. Quantum radiation efficiency reaches η = 10–12% for α-ZnSe and η = 5–8% for α-ZnS. The radiation is characterized by high temperature stability and repeatability of characteristics and parameters.